The Demographic Transformation of the Teaching Force in the United States - Richard Ingersoll; Elizabeth Merrill; Daniel Stuckey; Gregory Collins; Brandon Harrison (MDPI AG, 2021)
This article summarizes the results of an exploratory research project that investigated what demographic trends and changes have, or have not, occurred in the elementary and secondary teaching force in the U.S. over the past three decades, from 1987 to 2018. Our main data source was the Schools and Staffing Survey and its successor, the National Teacher Principal Survey, collectively the largest and most comprehensive source of data on teachers available in the U.S. These surveys are conducted by the National Center for Education Statistics (NCES), the statistical arm of the U.S. Department of Education. The results show that the teaching force has been, and is, greatly changing; yet, even the most dramatic trends appear to have been little noticed or understood by researchers, policy makers, and the public. This article summarizes seven of the most prominent trends and changes that we found. The U.S. teaching force is: larger; older; less experienced; more female; more diverse, by race/ethnicity; consistent in academic ability; unstable. For each of the trends, we explore two broad questions: 1. What are the reasons for and sources of the trend? 2. What are the implications and consequences of the trend?